Nano ceramic coating and preparation method thereof

By using nanoceramic coatings composed of ceramic powder, inorganic adhesive and linear thermal expansion coefficient regulator on the boiler, the problem of insufficient service life of the existing boiler coating in high temperature and high pressure environments is solved, and a higher life is achieved wear resistance, corrosion resistance and lower energy consumption and pollutant emissions.

CN119410178APending Publication Date: 2025-02-11GD POWER DEV CO LTD DALIAN DEV ZONE THERMAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411548805.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing boiler coating has little service life in high temperature and high pressure environments, and has insufficient wear and corrosion resistance, resulting in poor energy consumption and increased pollutant emissions.

Method used

The nanoceramic coating consisting of ceramic powder, inorganic adhesive and linear thermal expansion coefficient regulator is used to improve the wear and corrosion resistance of the coating through specific component ratios and preparation processes.

Benefits of technology

It significantly improves the wear and corrosion resistance of the boiler heating surface and furnace tube, reduces energy consumption and pollutant emissions, extends the service life of the boiler, and improves temperature uniformity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nano-ceramic coating and a preparation method thereof in the technical field of nano-ceramic coatings, the nano-ceramic coating is prepared from the following components: ceramic micro powder, an inorganic binder and a linear thermal expansion coefficient regulator, and the preparation method of the nano-ceramic coating is characterized in that the inorganic binder and the linear thermal expansion coefficient regulator are added into the nano-ceramic coating. Comprising the following steps: (1) preparing ceramic micro powder; (2) preparing a linear expansion coefficient regulator; (3) synthesizing an inorganic adhesive; (4) adding the ceramic micro powder, the inorganic adhesive and the linear expansion coefficient regulator into a coating synthesis kettle, and mixing; and (5) filtering and grinding the mixed coating to obtain the ceramic coating for the heating furnace. The invention has the advantages that the nano ceramic coating has the characteristics of corrosion resistance, wear resistance, optimized radiance and thermal shock resistance, high efficiency, energy conservation, prolonged service life of the lining furnace tube, improved temperature uniformity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano ceramic coatings, in particular to a nano ceramic coating and a preparation method thereof. Background Art

[0002] Energy conservation and consumption reduction is an important issue to solve the energy shortage of industrial production in my country. In particular, boilers and boiler equipment are key energy-consuming devices. Their energy conservation and consumption reduction is the best way to solve the energy shortage of industrial production in my country. In recent years, with the advancement of science and technology and the growth of industrial demand, people have higher and higher requirements for material performance, especially for the wear resistance and corrosion resistance of mechanical parts. Although traditional metal coatings have a certain protective effect, they perform poorly in extreme environments such as high temperature and high pressure, and are prone to wear, corrosion and other problems, which affect their service life. Summary of the invention

[0003] The technical problem to be solved by the present invention is that the existing boiler coating has poor energy consumption and a short service life.

[0004] To achieve the above purpose, the technical solution provided by the present invention is:

[0005] A nano ceramic coating is made of the following ingredients: 6.8-7.2 parts by mass of ceramic micropowder, 0.9-1.1 parts by mass of inorganic binder and 1.8-2.2 parts by mass of linear thermal expansion coefficient regulator, wherein the ceramic micropowder comprises 55-65% Fe2O3, 8-12% ZnO, 16-18% MnO2, 2-4% CrO3, 2-4% Ce2O3, 0.5-1.5% CaCO3 and 5-7% clay, the inorganic binder comprises aluminum sol, aluminum dihydrogen phosphate and sodium silicate, and the linear thermal expansion coefficient regulator comprises 40-60 parts by mass of cordierite powder and 60-40 parts by mass of cobalt chromate spinel powder.

[0006] Furthermore, the weight ratio of the cordierite powder to the cobalt chromate spinel powder is 1:1.

[0007] Furthermore, the particle size of the ceramic powder is less than 300 meshes.

[0008] Furthermore, the weight ratio of the ceramic powder, the inorganic binder and the linear expansion coefficient regulator is 7:1:2.

[0009] A method for preparing a nano ceramic coating comprises the following steps:

[0010] (1) Preparation of ceramic powder;

[0011] (2) Preparation of linear expansion coefficient regulator;

[0012] (3) Synthesizing an inorganic binder, adding aluminum sol into a reaction kettle, adding aluminum dihydrogen phosphate and sodium silicate for adjustment, and mixing and stirring for more than 3 hours;

[0013] (4) adding ceramic powder, inorganic binder and linear expansion coefficient regulator in a mass ratio of 7:1:2 into a coating synthesis kettle, stirring for more than 3 hours, filtering and discharging the mixed coating;

[0014] (5) The mixed coating obtained in step (4) is filtered and ground to obtain the ceramic coating for the heating furnace.

[0015] Furthermore, the preparation method of the ceramic powder is:

[0016] (a) mixing 55-65% Fe2O3, 8-12% ZnO, 16-18% MnO2, 2-4% CrO3, 2-4% Ce2O3, 0.5-1.5% CaCO3 and 5-7% clay, and adding water to prepare a thick slurry;

[0017] (b) applying the thick slurry evenly on the template, drying it naturally to form a thin sheet, placing the prepared thin sheet into a calcining furnace, calcining it at 1800-2500° C. for more than 2 hours, taking it out and rapidly cooling it to obtain a sheet;

[0018] (c) placing the material pieces into a pulverizer for preliminary pulverization to obtain a primary powder material of a predetermined particle size;

[0019] (d) adding the primary powder material to a fine grinding mill for fine grinding, adding the finely ground material to a sieving machine for sieving, obtaining a material with a particle size of less than 300 mesh as ceramic micro powder, and returning the material with a particle size of more than 300 mesh to the fine grinding operation unit for re-grinding.

[0020] Furthermore, the preparation of the linear expansion coefficient regulator includes preparing cordierite powder and preparing cobalt chromate spinel powder, wherein:

[0021] The preparation method of the cordierite powder is:

[0022] (a) dissolving aluminum nitrate and magnesium nitrate in water and mixing them uniformly by using a magnetic stirrer;

[0023] (b) dissolving tetraethyl orthosilicate in an ethanol solution, wherein the molar ratio of tetraethyl orthosilicate to ethanol is 0.8-1.2:3.5-4.5, to obtain a Si(OC2H5)4-C2H5OH solution;

[0024] (c) dropping aluminum nitrate and magnesium nitrate aqueous solution into Si(OC2H5)4-C2H5OH solution, stirring evenly to obtain a transparent sol, placing the transparent sol in an oven at 50-70°C for 8-12 hours to obtain a gel, drying and calcining to obtain cordierite powder;

[0025] The preparation method of the cobalt chromate spinel powder is:

[0026] (a) Dissolve citric acid in deionized water and stir vigorously for at least 0.4 hours to obtain a uniform solution A;

[0027] (b) Co(NO3)2·6H2O and Cr(NO3)3·9H2O in a molar ratio of 1:2 were prepared into a mixed solution, and the solution was vigorously stirred for at least 0.4 hours to obtain a uniform solution B;

[0028] (c) adding solution A dropwise into solution B and continuing stirring for at least 0.5 hours;

[0029] (d) subjecting the obtained solution to sol at 60-80° C. for at least 10 hours and drying and foaming at 100-150° C. for at least 5 hours to form a honeycomb xerogel;

[0030] (e) Grinding: calcining at least 600°C for at least 3 hours to obtain CoCr2CV.

[0031] Furthermore, in the preparation method of the cordierite powder, the aluminum nitrate, magnesium nitrate and ethyl orthosilicate are in the ratio of cordierite Mg2Al4Si5O 18 The stoichiometric ratio of ingredients.

[0032] The beneficial effects achieved by the present invention using the above structure are as follows:

[0033] The nano ceramic coating of the present invention has the advantages of improving the wear resistance and corrosion resistance of the boiler heating surface; reducing energy consumption and reducing pollutant emissions; improving the temperature uniformity in the heating furnace; improving the metallurgical stability of the boiler tube, delaying the coking and scaling of the tube, and maximizing the absorption capacity of the tube; and reducing the boiler furnace outer wall temperature and exhaust gas temperature. DETAILED DESCRIPTION

[0034] Embodiment 1:

[0035] A nano ceramic coating, which is made of the following ingredients: 6.9-7.1 parts by mass of ceramic micropowder, 0.95-1.15 parts by mass of inorganic binder and 1.9-2.1 parts by mass of linear thermal expansion coefficient regulator, wherein the components of the ceramic micropowder include 55-65% Fe2O3, 8-12% ZnO, 16-18% MnO2, 2-4% CrO3, 2-4% Ce2O3, 0.5-1.5% CaCO3 and 5-7% clay, and the particle size of the ceramic micropowder is less than 300 meshes, the inorganic binder includes aluminum sol, aluminum dihydrogen phosphate and sodium silicate, and the linear thermal expansion coefficient regulator includes 45-55 parts by mass of cordierite powder and 55-45 parts by mass of cobalt chromate spinel powder.

[0036] A method for preparing a nano ceramic coating comprises the following steps:

[0037] (1) Preparation of ceramic powder;

[0038] (2) Preparation of linear expansion coefficient regulator;

[0039] (3) Synthesizing an inorganic binder, adding aluminum sol into a reaction kettle, adding aluminum dihydrogen phosphate and sodium silicate for adjustment, and mixing and stirring for 3 hours;

[0040] (4) adding ceramic powder, inorganic binder and linear expansion coefficient regulator in a mass ratio of 7:1:2 into a coating synthesis kettle, stirring for 2 hours, filtering and discharging the mixed coating;

[0041] (5) The mixed coating obtained in step (4) is filtered and ground to obtain the ceramic coating for the heating furnace.

[0042] Furthermore, the preparation method of the ceramic powder is:

[0043] (a) mixing 55-65% Fe2O3, 8-12% ZnO, 16-18% MnO2, 2-4% CrO3, 2-4% Ce2O3, 0.5-1.5% CaCO3 and 5-7% clay, and adding water to prepare a thick slurry;

[0044] (b) applying the thick slurry evenly on the template, drying naturally to form a thin sheet, placing the prepared thin sheet into a calcining furnace, calcining at 1600-2400° C. for 2.5 hours, taking out and rapidly cooling to obtain a sheet;

[0045] (c) placing the material pieces into a pulverizer for preliminary pulverization to obtain a primary powder material of a predetermined particle size;

[0046] (d) adding the primary powder material to a fine grinding mill for fine grinding, adding the finely ground material to a sieving machine for sieving, obtaining a material with a particle size of less than 300 mesh as ceramic micro powder, and returning the material with a particle size of more than 300 mesh to the fine grinding operation unit for re-grinding.

[0047] The preparation of the linear expansion coefficient regulator includes preparing cordierite powder and preparing cobalt chromate spinel powder, wherein:

[0048] The preparation method of cordierite powder is:

[0049] (a) dissolving aluminum nitrate and magnesium nitrate in water and mixing them uniformly by using a magnetic stirrer;

[0050] (b) dissolving tetraethyl orthosilicate in an ethanol solution, wherein the molar ratio of tetraethyl orthosilicate to ethanol is 0.9-1.1:3.8-4.2, to obtain a Si(OC2H5)4-C2H5OH solution;

[0051] (c) dropping aluminum nitrate and magnesium nitrate aqueous solution into Si(OC2H5)4-C2H5OH solution, stirring evenly to obtain a transparent sol, placing the transparent sol in an oven at 55-65°C for 9-11 hours to obtain a gel, drying and calcining to obtain cordierite powder;

[0052] The preparation method of the cobalt chromate spinel powder is:

[0053] (a) Dissolve citric acid in deionized water and stir vigorously for 0.4 hours to obtain a uniform solution A;

[0054] (b) Co(NO3)2·6H2O and Cr(NO3)3·9H2O in a molar ratio of 1:2 were prepared into a mixed solution and vigorously stirred for 0.4 hours to obtain a uniform solution B;

[0055] (c) Add solution A dropwise into solution B and continue stirring for 0.5 h;

[0056] (d) the obtained solution was subjected to sol-gelation at 70° C. for 10 hours and dried and foamed at 130° C. for 5 hours to form a honeycomb dry gel;

[0057] (e) Grinding: Calcinate at 800°C for 3 hours to obtain CoCr2CV.

[0058] In the preparation method of cordierite powder, aluminum nitrate, magnesium nitrate and ethyl orthosilicate are mixed according to the ratio of cordierite Mg2Al4Si5O 18 The stoichiometric ratio of ingredients.

[0059] Embodiment 2:

[0060] A nano ceramic coating is made of the following ingredients: 7 parts by mass of ceramic micropowder, 1 part by mass of inorganic binder and 2 parts by mass of linear thermal expansion coefficient regulator, wherein the ceramic micropowder comprises 60% Fe2O3, 10% ZnO, 17% MnO2, 3% CrO3, 3% Ce2O3, 1% CaCO3 and 6% clay, and the particle size of the ceramic micropowder is less than 300 meshes, the inorganic binder comprises aluminum sol, aluminum dihydrogen phosphate and sodium silicate, and the linear thermal expansion coefficient regulator comprises 50 parts by mass of cordierite powder and 50 parts by mass of cobalt chromate spinel powder.

[0061] A method for preparing a nano ceramic coating comprises the following steps:

[0062] (1) Preparation of ceramic powder;

[0063] (2) Preparation of linear expansion coefficient regulator;

[0064] (3) Synthesizing an inorganic binder, adding aluminum sol into a reaction kettle, adding aluminum dihydrogen phosphate and sodium silicate for adjustment, and mixing and stirring for 3 hours;

[0065] (4) adding ceramic powder, inorganic binder and linear expansion coefficient regulator in a mass ratio of 7:1:2 into a coating synthesis kettle, stirring for 3 hours, filtering and discharging the mixed coating;

[0066] (5) The mixed coating obtained in step (4) is filtered and ground to obtain the ceramic coating for the heating furnace.

[0067] Furthermore, the preparation method of the ceramic powder is:

[0068] (a) 60% Fe2O3, 10% ZnO, 17% MnO2, 3% CrO3, 3% Ce2O3, 1% CaCO3 and 6% clay are mixed and water is added to prepare a thick slurry;

[0069] (b) applying the thick slurry evenly on the template, drying it naturally to form a thin sheet, placing the prepared thin sheet into a calcining furnace, calcining it at 2000° C. for 3 hours, taking it out and rapidly cooling it to obtain a sheet;

[0070] (c) placing the material pieces into a pulverizer for preliminary pulverization to obtain a primary powder material of a predetermined particle size;

[0071] (d) adding the primary powder material to a fine grinding mill for fine grinding, adding the finely ground material to a sieving machine for sieving, obtaining a material with a particle size of less than 300 mesh as ceramic micro powder, and returning the material with a particle size of more than 300 mesh to the fine grinding operation unit for re-grinding.

[0072] The preparation of the linear expansion coefficient regulator includes preparing cordierite powder and preparing cobalt chromate spinel powder, wherein:

[0073] The preparation method of cordierite powder is:

[0074] (a) dissolving aluminum nitrate and magnesium nitrate in water and mixing them uniformly by using a magnetic stirrer;

[0075] (b) dissolving tetraethyl orthosilicate in an ethanol solution, wherein the molar ratio of tetraethyl orthosilicate to ethanol is 1:4, to obtain a Si(OC2H5)4-C2H5OH solution;

[0076] (c) dropping aluminum nitrate and magnesium nitrate aqueous solution into Si(OC2H5)4-C2H5OH solution, stirring evenly to obtain a transparent sol, placing the transparent sol in an oven at 60° C. for 10 hours to obtain a gel, drying and calcining to obtain cordierite powder;

[0077] The preparation method of the cobalt chromate spinel powder is:

[0078] (a) Dissolve citric acid in deionized water and stir vigorously for 0.5 hours to obtain a uniform solution A;

[0079] (b) Co(NO3)2·6H2O and Cr(NO3)3·9H2O in a molar ratio of 1:2 were prepared into a mixed solution, and stirred vigorously for 0.5 hours to obtain a uniform solution B;

[0080] (c) Add solution A dropwise into solution B and continue stirring for 1 hour;

[0081] (d) the obtained solution was subjected to sol-gelation at 70° C. for 20 hours and dried and foamed at 130° C. for 7 hours to form a honeycomb dry gel;

[0082] (e) Grinding: Calcinate at 800°C for 4 hours to obtain CoCr2CV.

[0083] In the preparation method of cordierite powder, aluminum nitrate, magnesium nitrate and ethyl orthosilicate are mixed according to the ratio of cordierite Mg2Al4Si5O 18 The stoichiometric ratio of ingredients.

[0084] In summary: the nano ceramic coating of the present invention has the advantages of improving the wear resistance and corrosion resistance of the boiler heating surface; reducing energy consumption and reducing pollutant emissions; improving the temperature uniformity in the heating furnace; improving the metallurgical stability of the boiler tube, delaying the coking and scaling of the tube, and maximizing the absorption capacity of the tube; reducing the temperature of the outer wall of the boiler and the exhaust gas temperature. After spraying the ceramic coating of the present invention, the emissivity ε value can be increased to above 0.93, and the ε value increases slightly with the increase of temperature (the emissivity ε rises to 0.95-0.96 at 1100-1500°C), the coating thickness is 0.05-0.1mm, and the service life is 5 years. This material has the characteristics of high efficiency and energy saving, extending the service life of the boiler heating surface, shortening the heating time, and improving temperature uniformity.

[0085] The present invention and its implementation methods are described above, but such description is not restrictive. What is shown in the specific implementation is only one of the implementation methods of the present invention, and is not actually limited thereto. In short, if ordinary technicians in the field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A nano ceramic coating, characterized in that: The nano ceramic coating is made of the following ingredients: 6.8 to 7.2 parts by mass of ceramic micropowder, 0.9 to 1.1 parts by mass of inorganic binder and 1.8 to 2.2 parts by mass of linear thermal expansion coefficient regulator, wherein the components of the ceramic micropowder include 55 to 65% Fe2O3, 8 to 12% ZnO, 16 to 18% MnO2, 2 to 4% CrO3, 2 to 4% Ce2O3, 0.5 to 1.5% CaCO3 and 5 to 7% clay, the inorganic binder includes aluminum sol, aluminum dihydrogen phosphate and sodium silicate, and the linear thermal expansion coefficient regulator includes 40 to 60 parts by mass of cordierite powder and 60 to 40 parts by mass of cobalt chromate spinel powder.

2. A nano ceramic coating according to claim 1, characterized in that: The weight ratio of the ceramic powder, the inorganic binder and the linear expansion coefficient regulator is 7:1:

2.

3. A nano ceramic coating according to claim 2, characterized in that: The particle size of the ceramic micro powder is less than 300 meshes.

4. The nano ceramic coating according to claim 1, characterized in that: The weight ratio of the cordierite powder to the cobalt chromate spinel powder is 1:

1.

5. A method for preparing a nano ceramic coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of ceramic powder; (2) Preparation of linear expansion coefficient regulator; (3) Synthesizing an inorganic binder, adding aluminum sol into a reaction kettle, adding aluminum dihydrogen phosphate and sodium silicate for adjustment, and mixing and stirring for more than 3 hours; (4) adding ceramic powder, inorganic binder and linear expansion coefficient regulator in a mass ratio of 7:1:2 into a coating synthesis kettle, stirring for more than 3 hours, filtering and discharging the mixed coating; (5) The mixed coating obtained in step (4) is filtered and ground to obtain the ceramic coating for the heating furnace.

6. The method for preparing a nano ceramic coating according to claim 5, characterized in that: The preparation method of the ceramic micropowder is: (a) mixing 55-65% Fe2O3, 8-12% ZnO, 16-18% MnO2, 2-4% CrO3, 2-4% Ce2O3, 0.5-1.5% CaCO3 and 5-7% clay, and adding water to prepare a thick slurry; (b) applying the thick slurry evenly on the template, drying it naturally to form a thin sheet, placing the prepared thin sheet into a calcining furnace, calcining it at 1800-2500° C. for more than 2 hours, taking it out and rapidly cooling it to obtain a sheet; (c) placing the sheet into a pulverizer for preliminary pulverization to obtain a primary powder material of a predetermined particle size; (d) adding the primary powder material to a fine grinding mill for fine grinding, adding the finely ground material to a sieving machine for sieving, obtaining a material with a particle size of less than 300 mesh as ceramic micro powder, and returning the material with a particle size of more than 300 mesh to the fine grinding operation unit for re-grinding.

7. The method for preparing a nano ceramic coating according to claim 5, characterized in that: The preparation of the linear expansion coefficient regulator includes preparing cordierite powder and preparing cobalt chromate spinel powder.

8. The method for preparing a nano ceramic coating according to claim 7, characterized in that: The preparation method of the cordierite powder is: (a) dissolving aluminum nitrate and magnesium nitrate in water and mixing them uniformly by using a magnetic stirrer; (b) dissolving tetraethyl orthosilicate in an ethanol solution, wherein the molar ratio of tetraethyl orthosilicate to ethanol is 0.8-1.2:3.5-4.5, to obtain a Si(OC2H5)4-C2H5OH solution; (c) Aqueous solutions of aluminum nitrate and magnesium nitrate are dropped into Si(OC2H5)4-C2H5OH solution, and stirred evenly to obtain a transparent sol. The transparent sol is placed in an oven at 50-70°C for 8-12 hours to obtain a gel, which is then dried and calcined to obtain cordierite powder.

9. The method for preparing a nano ceramic coating according to claim 7, characterized in that: The preparation method of the cobalt chromate spinel powder is: (a) Dissolve citric acid in deionized water and stir vigorously for at least 0.4 hours to obtain a uniform solution A; (b) Co(NO3)2·6H2O and Cr(NO3)3·9H2O in a molar ratio of 1:2 were prepared into a mixed solution, and the solution was vigorously stirred for at least 0.4 hours to obtain a uniform solution B; (c) adding solution A dropwise into solution B and continuing stirring for at least 0.5 hours; (d) subjecting the obtained solution to sol at 60-80° C. for at least 10 hours and drying and foaming at 100-150° C. for at least 5 hours to form a honeycomb xerogel; (e) Grinding: calcining at least 600°C for at least 3 hours to obtain CoCr2CV.

10. The method for preparing a nano ceramic coating according to claim 8, characterized in that: In the preparation method of cordierite powder, aluminum nitrate, magnesium nitrate and ethyl orthosilicate are mixed according to the ratio of cordierite Mg2Al4Si5O 18 The stoichiometric ratio of ingredients.

Citation Information

Patent Citations

  • Ceramic coating used for heating furnace

    CN102020475A